Penggunaan Video Comment dalam Meningkatkan Minat Belajar Peserta Didik Mapel PAI di SDN 4 Mrayan Ngrayun Ponorogo Tahun Pelajaran 2023/2024 - Tri Cahyono, Hasan; Fanani, Moh. Zainal; Rosikin (Allimna: Jurnal Pendidikan Profesi Guru, 2024)
This Classroom Action Research (CAR) aims to explore the effectiveness of using Video Comment as a learning medium in enhancing students' interest in Islamic Education subject at SDN 4 Mrayan Ngrayun Ponorogo for the academic year 2023/2024. Recognizing the need for innovation in the learning process dynamics, this study identifies that students' learning interest can be a crucial indicator in achieving an effective and efficient learning process. Implemented in three cycles, this research collected data through observation, interviews, and document analysis to assess changes in students' learning interest since the implementation of Video Comment. The findings indicate a significant increase in students' learning interest from the pre-cycle with a learning interest of 36%, rising to 61% in cycle I, 69% in cycle II, and reaching an average of 78% in cycle III. This increase signifies that the integration of Video Comment in the learning process contributes positively to enhancing students' learning interest. Further analysis reveals that Video Comment successfully provides engaging and interactive content that facilitates students' involvement in the learning material. Moreover, the study identifies supporting and inhibiting factors in the use of Video Comment, where 94% of students showed an increase in learning interest as a direct result of this innovative learning process. The conclusion of this study underscores the importance of using innovative learning media, such as Video Comment, in boosting students' learning interest. The practical implications of this research offer insights for educators to integrate relevant learning technologies with modern students' needs, as a strategy to improve the quality of the learning process in today's educational environment.